АНАЛИЗ СУТОЧНОГО МОНИТОРИРОВАНИЯ АРТЕРИАЛЬНОГО ДАВЛЕНИЯ У БОЛЬНЫХ С СОМАТОТРОПИНОМОЙ - Ю. В. Завьялова; Н. Н. Боровков; О. В. Занозина (Архивъ внутренней медицины, 2014)
The analysis of changes in indicators ambulatory blood pressure monitoring (ABPM) in 26 patients with somatotropinoma. In 2/3 patients recorded systolic and diastolic hypertension. When analyzing their circadian blood pressure (BP) drew the attention of the lack of blood pressure reduction at night.